A Cross-sectional Study on Knowledge of Monkeypox Disease (MPOX) Among Young Adults - Deepak Subedi; Alok Dhakal; Sumit Jyoti; Sanju Subedi; Deepak Chandran; Vinodhini Duraisamy; Mohammed S. Almuhayawi; Mohammed K. Nagshabandi; Muyassar K. Tarabulsi; Soad K. Al Jaouni; Samy Selim (Journal of Pure and Applied Microbiology, 2024)
The 2022 Monkeypox Disease (MPOX) outbreak was declared a pandemic after detecting multiple human-to-human monkeypox cases in ‘non-endemic’ nations. The index case of MPOX has been reported in Nepal. Also, the disease burden in neighboring countries and international travel and tourism could increase the MPOX burden in Nepal. This study recruited 443 study participants between August 25 and September 10, 2022, using the snowball technique and using descriptive statistics to assess the awareness and knowledge of MPOX. Approximately 82% (n=361) of the study participants were young adults aged between 18-29 years and were undergoing or holders of tertiary education degrees (72.2%, n=320). Our findings showed that 76.5% (n=339/443) of the respondents were aware of the 2022 MPOX outbreak and obtained information about the disease from their local radio and television stations (20.6%, n = 70), as well as from other sources such as social media platforms (70.5%, n=239), and other internet sources (61.6%, n=209). The mean knowledge score of the respondents was 3.95±1.26, with a range of 0.5 to 7. Approximately three-quarters (72.3%, n=245) of the study participants were graded to have a good knowledge of the MPOX. Of the listed symptoms, study participants correctly identified high fever (62.2%, n=339), rashes (51.0%, n=173), swollen lymph nodes (34.5%, n=117), and sores around the mouth, vagina, and anus (26.8%, n=91). A higher number of participants were aware that vaccination could confer protection against the disease (70.8%, n=240). However, less than one third of the participants (30%, n=102) were aware that safe sex practices can be a preventive strategy against the disease. Finally, none of the sociodemographic variables were associated with increased knowledge of MPOX among the study participants. The knowledge of MPOX among the study population was above average. We advocate that public enlightenment campaigns in Nepal should address wrong perceptions of MPOX.